Embedding of Circulant Networks Into Cycle-of-butterfly - Packiaraj, L; Manoj, K (International Journal of Computer Sciences and Engineering, 2025)
Circulant networks is one of most popular interconnection networks since it has a simple structure and •s easy to implement. Graph embedding is an important parameter to evaluate the qual•ty of an interconnection network and wirelength is an important measure of an embedding. In this paper, we embed circulant network into cycle-of-butterfly with minimum wirelength